2021
DOI: 10.3389/fpsyg.2021.638938
|View full text |Cite
|
Sign up to set email alerts
|

Couples Coping With the Serious Illness of One of the Partners

Abstract: Chronic kidney failure is a serious somatic disease. Addressing the issue of living with a chronic disease means fully considering the patients’ entourage, their families, and those close to them, especially their children and spouses.Objectives: The present paper focuses on the couple’s psychological experience when one of them suffers from a chronic disease, in this instance kidney disease. In particular, how is the spouse affected by the treatment provided? The aim is not only to see how care for sick peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Substantial evidence suggests that the quality of intimate relationships affects the mental health of partners ( Baucom et al, 2012 ). However, illness can disrupt the daily lives of couples and families, leading to significant burdens and suffering for partners ( Riazuelo, 2021 ). Findings from a multicentre longitudinal study ( Moore et al, 2020 ) reveal that while participants reported improved quality of life after starting dialysis, partners experienced worsened quality of life initially, showing improvement after 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence suggests that the quality of intimate relationships affects the mental health of partners ( Baucom et al, 2012 ). However, illness can disrupt the daily lives of couples and families, leading to significant burdens and suffering for partners ( Riazuelo, 2021 ). Findings from a multicentre longitudinal study ( Moore et al, 2020 ) reveal that while participants reported improved quality of life after starting dialysis, partners experienced worsened quality of life initially, showing improvement after 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The patients in this study expressed their dependence on their family's assistance, particularly in terms of physical mobility and fulfilling their daily responsibilities, including religious obligations and household tasks. Numerous studies have highlighted the significance of family social support in the daily routines of chronically ill patients, irrespective of their specific condition Tedesse et al, 2020;Ng et al, 2020;Darwish et al, 2020;Riazuelo, 2021). Because of their health issues, especially the lack of physical strength, they must adapt their ibadah style according to the guidelines provided by Islam, which accommodate the ease and capabilities of patients known as rukhsah (Arif et al, 2014;Yusop, et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, other research subjects showed great adaptability even though their partners were seriously ill and being treated. Consultation and support provided by people around them, makes it easier for someone to overcome anxiety 20 . Adaptive behavior, perception, cognition, motivation synchronized from cortical and subcortical neural networks are modulated by the role of the amygdala 15 .…”
Section: Discussionmentioning
confidence: 99%